CHANGE OF PARADIGM IN LATVIA EDUCATIONAL ESTABLISHMENT MANAGEMENT IN HISTORICAL PERSPECTIVE (FROM 1919 TO 1940) - Jurs, Pāvels; Kulberga, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Independence and freedom of Latvia State since the proclamation of the Republic of Latvia in 1918 was interrupted by World War II. During that time the education system of Latvia has also changed, including fundamental principles of educational institution management. The goal of the article is to analyse changes in educational institution management in historical perspective, comparing legal regulations in two periods of Latvia: in the democratic (1919) and authoritarian (1934) regime of the First Free State of the Latvia Republic. In the article the theoretical research methods (method of comparison and critical thinking) and empirical research methods (data collection method and document analysis) have been applied. Comparing the periods of the democratic (from 1919 to 1934) and authoritarian regime (from 1934 to 1940) of the First Free State of the Latvia Republic in the context of educational institution management, it should be mentioned that the legislation of the authoritarian regime envisaged much broader responsibility, duties and rights for the head of the school. Moreover, the head of the school could also have deputies depending on the size of the school. The structure of educational institution management in the authoritarian regime in comparison with the democratic regime was more particular, with a more detailed description of responsibilities, with an increased parents’ involvement in the school life organization.